2021
DOI: 10.1111/tpj.15247
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of bundle sheath electron transport capacity under limiting light in C4Setaria viridis

Abstract: SUMMARY C4 photosynthesis is a biochemical pathway that operates across mesophyll and bundle sheath (BS) cells to increase CO2 concentration at the site of CO2 fixation. C4 plants benefit from high irradiance but their efficiency decreases under shade, causing a loss of productivity in crop canopies. We investigated shade acclimation responses of Setaria viridis, a model monocot of NADP‐dependent malic enzyme subtype, focussing on cell‐specific electron transport capacity. Plants grown under low light (LL) mai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 80 publications
4
32
0
Order By: Relevance
“…This review focuses on the photosynthetic light‐dependent reactions, the optimization of which is relevant to improving both C3 and C4 photosynthesis in plants and photosynthetic micro‐organisms (Leister, 2012; Ruban, 2015; von Caemmerer and Furbank, 2016; Cardona et al, 2018; Simkin et al, 2019; Batista‐Silva et al, 2020; Ermakova et al, 2021b; Sales et al, 2021; Santos‐Merino et al, 2021). Modeling studies have suggested that improving the quantum yield and electron transport capacity have a greater potential for increasing the productivity of crops than other photosynthetic mechanisms, such as improving Rubisco activity (Gu et al, 2014; Yin and Struik, 2015, 2021a; Wu et al, 2019).…”
Section: Introduction—why Do We Need Crops With Increased Yields?mentioning
confidence: 99%
“…This review focuses on the photosynthetic light‐dependent reactions, the optimization of which is relevant to improving both C3 and C4 photosynthesis in plants and photosynthetic micro‐organisms (Leister, 2012; Ruban, 2015; von Caemmerer and Furbank, 2016; Cardona et al, 2018; Simkin et al, 2019; Batista‐Silva et al, 2020; Ermakova et al, 2021b; Sales et al, 2021; Santos‐Merino et al, 2021). Modeling studies have suggested that improving the quantum yield and electron transport capacity have a greater potential for increasing the productivity of crops than other photosynthetic mechanisms, such as improving Rubisco activity (Gu et al, 2014; Yin and Struik, 2015, 2021a; Wu et al, 2019).…”
Section: Introduction—why Do We Need Crops With Increased Yields?mentioning
confidence: 99%
“…S. viridis uses NADPH-dependent malic enzyme (NADP-ME) decarboxylation system in the bundle sheath chloroplast (Fig. 6) and, similar to most of NADP-ME species, S. viridis has low PSII activity and linear electron transport rate in bundle sheath cells (Ermakova et al, 2021a). This prompts export of part of the 3-phosphoglycerate (3-PGA) pool to the mesophyll for conversion to triose phosphate, which then diffuses back to the bundle sheath, known as the triose phosphate shuttle (von Caemmerer and Furbank, 2016 and references therein) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…BS strands were isolated following the procedure of Ghannoum et al (2005) as described in detail in Ermakova et al (2021a). RNA was isolated from leaves and BS strands, ground in liquid N 2 , using the RNeasy Plant Mini Kit (Qiagen, Venlo, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…The vast majority of agriculturally important C4 crops, like maize, sorghum (Sorghum bicolor), sugarcane, miscanthus and several millets (e.g., Setaria italica), belong to the NADP-ME subtype of C4 photosynthesis which employs NADP + -dependent malic enzyme to decarboxylate the C4 acid malate in BS chloroplasts (Furbank, 2011). Because of the drastic differences in biochemistry of mesophyll and BS cells in NADP-ME plants, electron transport chains of the two cell types are also largely different: mesophyll cells predominantly run linear electron flow and BS cells -cyclic electron flow (Ermakova et al, 2021a;Munekage, 2016). To coordinate the production of NADPH and ATP between cells, plants need to tightly regulate the distribution of available light energy (Bellasio and Ermakova, 2021;Bellasio and Lundgren, 2016).…”
Section: Introductionmentioning
confidence: 99%